Design and evaluation of polarity controlled and recyclable deep eutectic solvent based biphasic system for the polarity driven extraction and separation of compounds. (20th September 2020) - Tang, Weiyang; Row, Kyung Ho
Abstract: Deep eutectic solvent (DES) based extraction methods have promising applications in extracting and separating compounds from plants. In this study, a polarity controlled biphasic extraction system consisting of a hydrophilic DES phase (Hexafluoroisopropanol-choline chloride: HFIP-ChCl) and a hydrophobic DES phase (Menthol-tricaprylylmethylammonium chloride: Menthol-N8881 Cl) was constructed. The DES based biphasic system was successful in the simultaneous extraction and separation of high polarity compounds, such as chlorogenic acid (CHA), quercetin (QUE) and anthocyanidins (ANT), and a low polarity compound artemisinin(ART), from Artemisia annua Leaves in a single step by the polarity driven recognition targets. By adjusting the mole ratio of the component in each DES phase, the HFIP-ChCl(1:1)/Menthol-N8881 Cl(2:1) biphasic system showed the best extraction and separation performance. A conductor-like screening model for real solvents (COSMO-RS) was used to monitor and analyze the changes in the surface polarity dynamics of each DES. The results showed that the non-polar intensity increased from 11.89 to 21.06 Å 2 with increasing proportion of HFIP in HFIP-ChCl and the non-polar intensity weakened from 16.47 to 10.01 Å 2 with increasing proportion of Menthol in Menthol-N8881 Cl. This model can be efficient for screening suitable DESs in a DES based biphasic extraction system to accommodate compounds with a range of polarities. Supported by the model and experimental data of the DES based biphasic system, 6.21 mg/g ART was transferred to the upper layer (Menthol-N8881 Cl with 2:1 mol ratio) and 7.89 mg/g CHA, 5.5 mg/g QUE, and 8.9 mg/g ANT were transferred to the lower layer (HFIP-ChCl with 1:1 mol ratio) under the optimal condition (15/1 solvent/solid ratio, 40 °C extraction temperature, 1:1 vol ratio and 30 min extraction time). Therefore, the polarity controlled DES based biphasic extraction system was used to expand the application of DESs in the extraction and separation of bioactive compounds with various polarities. Graphical abstract: Image 1 Highlights: A polarity controlled and recyclable DES based biphasic extraction system was constructed. DES biphasic system achieved the simultaneous extraction and separation of various polarities compounds. COSMO-RS was used to monitor and analyze the changes in the surface polarity dynamic of each DES. The DES biphasic system can be recycled and reused to separate compounds of different polarities.